Performance Psychology in Action : a Casebook for Working with Athletes, Performing Artists, Business Leaders, and Professionals in High-Risk Occupations - Hays, Kate F. (American Psychological Association, 2009)
"Expert athletes understand the mind-body connection. For years, they have learned mental skills from coaches, consultants, and other practitioners in order to optimize physical performance. Now, these same mental skills are being taught to a broad range of professionals, such as dancers, actors, lawyers, surgeons, business leaders, and rescue workers. The resulting new field of performance psychology allows performers from a variety of fields to "get their head out of the way so that their body can do what it's trained to do." This book describes the everyday practice of performance psychology. Case by case, stories demonstrate how consultants have helped performers develop confidence, overcome mental blocks, manage emotions, and use preparation techniques such as imagery and positive self-talk to achieve the best possible mental state for performance. The chapters blend theory and practice, integrating literature reviews with real-world applications; they cover a wide range of performers, including athletes, performing artists, business leaders, and professionals in high-risk occupations. Extensive session transcripts are provided, including the consultants' thoughts and reactions throughout the session. Engaging, nuanced, personal, and highly accessible, this book will help practitioners and students from a variety of fields explore performance psychology ... in action"--Jacket. (PsycINFO Database Record (c) 2009 APA, all rights reserved).